1995
DOI: 10.1111/j.1532-5415.1995.tb06392.x
|View full text |Cite
|
Sign up to set email alerts
|

Pancytopenia and Valproic Acid—a Possible Association

Abstract: To the Editor: Valproic acid was approved in the US for use as an antiepileptic in 1978. Pharmacologically it has antiepileptic activity against a variety of seizure types while causing minimal central nervous system side effects.' Although the mechanism of action of valproic acid is unknown, evidence suggests that valproic acid selectively increases concentrations of gamma-aminobutyric acid in synaptic regions.' Valproic acid's psychopharmacological indications have expanded to include use for mood stabilizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Kishi et al (1994) have shown that a high plasma VPA concentration is associated with in vivo and in vitro bone marrow suppression. While the VPA concentration‐dependent thrombocytopenia could be explained by the mechanism of bone marrow suppression, the rare occurrence of pancytopenia suggests that other mechanisms must be involved that renders the platelet cell lineage more vulnerable to VPA suppression or damage (Robinson et al, 1995; Oluboka et al, 2000). It is possible that both immune‐mediated peripheral destruction and VPA concentration‐dependent suppression of platelet precursors may be operating simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…Kishi et al (1994) have shown that a high plasma VPA concentration is associated with in vivo and in vitro bone marrow suppression. While the VPA concentration‐dependent thrombocytopenia could be explained by the mechanism of bone marrow suppression, the rare occurrence of pancytopenia suggests that other mechanisms must be involved that renders the platelet cell lineage more vulnerable to VPA suppression or damage (Robinson et al, 1995; Oluboka et al, 2000). It is possible that both immune‐mediated peripheral destruction and VPA concentration‐dependent suppression of platelet precursors may be operating simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…Robinson et al have proposed that age, illness, and medications may create a synergistic vulnerability to hemopoietic disorders 14 . Duration of exposure and dose of valproic acid may also be significant risk factors in the development of valproic acid‐induced pancytopenia.…”
mentioning
confidence: 99%
“…Severe valproic acid poisoning primarily affects the cardiovascular and central nervous systems 10–17 . Severe hemolysis has never been reported with valproic acid toxicity.…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…[6][7][8][9] Severe valproic acid poisoning primarily affects the cardiovascular and central nervous systems. [10][11][12][13][14][15][16][17] Severe hemolysis has never been reported with valproic acid toxicity. Thrombocytopenia is the most common hematologic abnormality found with acute Valproate toxicity.…”
Section: Discussion and Resultsmentioning
confidence: 99%
See 1 more Smart Citation